Scaramuccia nel teatro di strada. Una proposta di ‘attribuzionismo teatrale’ - Natalia Gozzano (Drammaturgia)
In the Museo di Roma at Palazzo Braschi there is a painting attributed to an anonymous Flemish painter of the 17th century depicting a theatre scene in Piazza Pasquino, whose iconography differs from the usual depiction of this subject spread by bamboozling painters in the 17th century.